Comparative Mitogenomics in Hyalella (Amphipoda: Crustacea) - Zapelloni, Francesco (Genes (Basel), 2021)
We present the sequencing and comparative analysis of 17 mitochondrial genomes of Nearctic and Neotropical amphipods of the genus Hyalella, most from the Andean Altiplano. The mitogenomes obtained comprised the usual 37 gene-set of the metazoan mitochondrial genome showing a gene rearrangement (a reverse transposition and a reversal) between the North and South American Hyalella mitogenomes. Hyalella mitochondrial genomes show the typical AT-richness and strong nucleotide bias among codon sites and strands of pancrustaceans. Protein-coding sequences are biased towards AT-rich codons, with a preference for leucine and serine amino acids. Numerous base changes (539) were found in tRNA stems, with 103 classified as fully compensatory, 253 hemi-compensatory and the remaining base mismatches and indels. Most compensatory Watson–Crick switches were AU -> GC linked in the same haplotype, whereas most hemi-compensatory changes resulted in wobble GU and a few AC pairs. These results suggest a pairing fitness increase in tRNAs after crossing low fitness valleys. Branch-site level models detected positive selection for several amino acid positions in up to eight mitochondrial genes, with atp6 and nad5 as the genes displaying more sites under selection.